(3GdfGaY aj (B[(3cjajI JYdje(B] (3UfGYI GdWHs - (3Ydj Hf QVhGf Hf Ydj Hf LYaQ, CHh GdMSf,J (B453 (3g` s
(3ChdgG (B:s
(3Ef bUOfG Gf fHjf eG GdfGaY aj JYdje UfGYI GdWH , hPdc Gfg YQV dfG aj JYdjegG ZjQI YXjeI s
(3BNQgG (B:s
(3hEdi Cf JUjQ WHjH aGVdkG , ajdShakG cGedkG , Ef TGA Gddg s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3QJHg Ydi KeGfjI CHhGHs
(3Vef eLehY eDQN SfI (B1196 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B94s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B192 s
Keywords: (3GdWHs